2018
DOI: 10.1090/tran/7692
|View full text |Cite
|
Sign up to set email alerts
|

Some examples of composition operators and their approximation numbers on the Hardy space of the bidisk

Abstract: We give examples of composition operators C Φ on H 2 (D 2 ) showing that the condition Φ ∞ = 1 is not sufficient for their approximation numbers a n (C Φ ) to satisfy lim n→∞ [a n (C Φ )] 1/ √ n = 1, contrary to the 1-dimensional case.We also give a situation where this implication holds. We make a link with the Monge-Ampère capacity of the image of Φ.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 24 publications
0
25
0
Order By: Relevance
“…Another application of weighted composition operators to the study of composition operators on spaces of several complex variables can be found in[29].…”
mentioning
confidence: 99%
“…Another application of weighted composition operators to the study of composition operators on spaces of several complex variables can be found in[29].…”
mentioning
confidence: 99%
“…In any case, this lets us suspect that the formula of Theorem 4.1 holds in much more general cases. This is not quite true, as evidenced by our counterexample of [41,Theorem 5.12]. Nevertheless, in good cases, this formula holds, as we will see in the next sections.…”
Section: The Spectral Radius Type Formulamentioning
confidence: 81%
“…In [41], we pursued that line of investigation in dimension N ≥ 2, namely on H 2 (D N ), and showed that in some cases the implication (1.2) still holds ([41, Theorem 3.1]):…”
Section: Introductionmentioning
confidence: 99%
“…It is coined in [1] (see also [13] and [14]) that β ± N (C Φ ) are the suitable parameters for the composition operators on H 2 (D N ), and it is proved, for any N ≥ 1, that β − N (C Φ ) > 0, as soon as Φ is non degenerate (i.e. the Jacobian J Φ is not identically 0) and the operator C Φ is bounded on H 2 (D N ).…”
Section: Introductionmentioning
confidence: 99%
“…the Jacobian J Φ is not identically 0) and the operator C Φ is bounded on H 2 (D N ). As for an expression of β ± N (C Φ ) in terms of "capacity", only partial results are known so far ( [13] and [14]) and the application to a result like (1.1) fails in general. We gave an example of such a phenomenon in [13,Theorem 5.12].…”
Section: Introductionmentioning
confidence: 99%